Synthesis and Molecular Docking Study of 4-(3-(2-Chlorophenyl)-5-(2-Methoxyphenyl)-4,5-Dihydro-1H-Pyrazol-1-yl) Benzenesulfonamide as Antibreast Cancer Agent - Eka Marisa Putri; Noval Herfindo; Guntur Guntur; Neni Frimayanti; Adel Zamri (ALCHEMY Jurnal Penelitian Kimia, 2021)
Breast cancer is a disease in which cells in the breast tissue change and divide in an uncontrolled way. Pyrazoline is a promising agent reported against cancer. In this work, we have synthesized pyrazoline 4-(3-(2-chlorophenyl)-5-(2-methoxyphenyl)-4,5-dihydro-1H-pyrazol-1-yl) benzenesulfonamide (EMP-1). The reaction was successfully carried out in one-pot three components from 2-chloroacetophenone, 2-methoxybenzaldehyde, and 4-hydrazinylbenzenesulfonamide as starting materials. The reaction was conducted by assisting the irradiation of Monowave 50 (Anton-Paar) with a high yield of 91%. Its potential anti-breast cancer was investigated by molecular docking and dynamic studies. The molecular docking study showed that EMP-1 had binding energy of -7.17 kcal/mol. The spatial arrangement of EMP-1 was similar to the positive control of doxorubicin. These results indicate that EMP-1 compound potentially developed as anti-breast cancer.